TENSILE PROPERTIES AND MICROSTRUCTURES OF HYBRID UNIDIRECTIONAL COIR/CARBON FIBRE-REINFORCED EPOXY COMPOSITES - Madueke, Chioma Ifeyinwa; Umunakwe, Reginald; Yemi, Audu (FUDMA JOURNAL OF SCIENCES, 2025)
Bio-fibres from plants as well as fibres from other natural materials have been immensely exploited for use as reinforcements in composites. The aim of this work is to determine the tensile properties of hybrid unidirectional coir/carbon fibre reinforced epoxy composites manufactured via hand layup. Coconut from which coir (coconut fibre) is obtained is abundant in Nigeria. Coir is a lignocellulosic fibre known for its relatively low density and thus savings in energy hence recommendable for light weight applications. Being a natural fibre, it is also eco-friendly. Carbon fibre (T700 Carbon) is a synthetic fibre notable for its high strength. The study seeks to harness the potential of hybridizing coir with carbon as reinforcements to improve the tensile properties of the epoxy composites. This work also advances beyond existing studies on similar composites via the unique stacking sequences. The average tensile strength, Young’s modulus and elongation at break were obtained from three different stacking sequences: Carbon-Carbon-Coir-Coir-Carbon-Carbon, Coir-Carbon-Coir and Carbon Coir Carbon. The stacking sequence that exerted the highest influence on the tensile properties of the manufactured composites was found to be Carbon-Carbon-Coir-Coir-Carbon-Carbon with the tensile strength 63 and 34% higher than those of Coir-Carbon-Coir and Carbon-Coir-Carbon respectively. However the stiffness of Coir-Carbon–Coir was 26% higher than that of Carbon-Coir-Carbon. Therefore, improved mechanical properties of hybrid coir/carbon composites can be achieved using stacking sequence: carbon-carbon-coir-coir-carbon-carbon. The morphology of the coir and carbon and the failure modes of the composites were also carefully investigated.